Expanding Thinking Through a Kaleidoscopic Look Into the Future: Implications of the Mixed Methods International Research Association's Task Force Report on the Future of Mixed Methods. (July 2016) - Mertens, Donna M.; Bazeley, Patricia; Bowleg, Lisa; Fielding, Nigel; Maxwell, Joseph; Molina-Azorin, José F.; Niglas, Katrin
The field of mixed methods research abounds with opportunities for creative development in terms of methodological advances and potential to contribute to important and complex societal problems. Inspired by issues that arose in the Mixed Methods International Research Association task force report on the future of mixed methods, this article contemplates its implications for challenges and opportunities for the mixed methods community for advancement in philosophy and methodology, innovative designs, technological advancements and big data, preparation of mixed methods researchers, and responsiveness to complex societal problems. We invite the mixed methods research community to participate in the conversation about these important, as yet unanswered, questions relevant for the future of mixed methods research and the world.